Can FLIP guide therapy in idiopathic esophagogastric junction outflow obstruction?. Issue 4 (2nd December 2021) - Beveridge, Claire A; Triggs, Joseph R; Thanawala, Shivani U; Ahuja, Nitin K; Falk, Gary W; Benitez, Alain J; Lynch, Kristle L
Abstract: Background: Esophagogastric junction outflow obstruction (EGJOO) has a variable disease course. Currently, barium swallow (BaS) and manometric parameters are used to characterize clinically significant EGJOO. The esophagogastric junction distensibility index (EGJ-DI) measured via functional lumen imaging probe (FLIP) can provide complementary information. Our aim was to assess symptom response in patients with EGJOO and an abnormal EGJ-DI after botulinum toxin (BT) treatment. Methods: A prospective cohort study of adults with idiopathic EGJOO was performed from September 2019 to March 2021. Patients with dysphagia underwent upper endoscopy with FLIP. If the EGJ-DI was abnormally low, BT was injected. Data examined included demographics, medical history, endoscopic and FLIP findings, BaS, manometry, and Eckardt score (ES). ES improvement was assessed via paired samples t -test. Pearson's chi-square tests were used to assess for associations. Results: Of the 20 patients, 75% had an abnormal EGJ-DI and underwent BT injections. Mean ES for patients with abnormal EGJ-DIs significantly improved from baseline to 1, 3, and 6 month follow-up ( P -values: 0.01, 0.05, and 0.02, respectively). There was a significant association between an abnormal EGJ-DI with delayed bolus transit and presence of rapid drink challenge panesophageal pressurization on manometry: P = 0.03 and P = 0.03. Conclusion: This prospective study revealed that an abnormal EGJ-DI can guide BT as assessed via symptomatic response. Additionally, abnormal EGJ-DI measurements were significantly associated with other parameters used previously to determine clinically relevant EGJOO. Larger follow-up studies are warranted to further elucidate guidance for therapy in EGJOO.